2001
DOI: 10.1002/cncr.9049
|View full text |Cite
|
Sign up to set email alerts
|

Microphthalmia transcription factor

Abstract: Transfer request: A self‐assembled supramolecular charge‐transfer complex of 1‐(11‐oxo‐11‐pyren‐1‐ylmethoxy)undecyl)pyridinium bromide (PYR) and ethane‐1,2‐diyl bis(3,5‐dinitrobenzoate) (DNB) is shown to form vesicular aggregates in aqueous solution, in contrast to the tubular aggregates of pure PYR (see picture). A curvature‐dependent mechanism for this change is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…In this small number of SLNs, Mitf demonstrates a specificity of 100%. This is comparable to a specificity of 97% as described by Sheffield et al in 72 primary melanomas and 32 nonmelanocytic malignancies [6] and a specificity of 100% as found by Dorvault et al [14]. Miettinen et al suggest caution in the use of Mitf in the search for nodal micrometastasis as they found occasional Mitf-positive nuclei in histiocytes of germinal centers in 8 out of 20 lymph nodes and in sinus histiocytes in 7 out of 22 lymph nodes.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…In this small number of SLNs, Mitf demonstrates a specificity of 100%. This is comparable to a specificity of 97% as described by Sheffield et al in 72 primary melanomas and 32 nonmelanocytic malignancies [6] and a specificity of 100% as found by Dorvault et al [14]. Miettinen et al suggest caution in the use of Mitf in the search for nodal micrometastasis as they found occasional Mitf-positive nuclei in histiocytes of germinal centers in 8 out of 20 lymph nodes and in sinus histiocytes in 7 out of 22 lymph nodes.…”
Section: Discussionsupporting
confidence: 63%
“…In mice, the allele Mitf mi leads to complete absence of melanocytes in the homozygous state [12]. In contrast to various melanocytic markers, such as melanin or c-kit, whose expression may be lost or difficult to detect in malignant melanocytic lesions, Mitf expression is usually maintained in human melanoma specimens [7,9,10,11,13,14]. Different signaling molecules or transcription factors implicated genetically in melanocyte development are known to either affect Mitf expression or its function [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 serial 4‐μm sections were also prepared from one cut face of the node by the method described by Cochran et al. , 3 and stained in sequence with HE for S‐100 protein, with HE for HMB‐45, and with HE for Melan‐A 6–13 (Table 2). Immunostaining for S‐100 protein, HMB‐45 and Melan‐A was performed by the avidin‐biotin‐peroxidase complex (ABC) method.…”
Section: Case Reportmentioning
confidence: 99%
“…However, the diagnostic utility of this immunostain is limited by broad expression of its target antigen in other cell types of neural crest origin and its failure to stain up to 7% of melanomas. 16 Melan-A (and its closely related antigen MART-1) is a commonly used alternative to S100 because of its perceived high sensitivity and specificity for melanocytes. Recent studies, though, have suggested that Melan-A overestimates the number of melanocytes in solar lentigenes and MIS, and stains keratinocytes in the setting of inflammation.…”
Section: Introductionmentioning
confidence: 99%